Growth, proximate composition, and metabolism of rainbow trout (Oncorhynchus mykiss) consuming diets containing alternative proteins - Craft, Christopher D., author; Myrick, Christopher, advisor; Engle, Terry, committee member; Winkelman, Dana, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: fish metabolism; rainbow trout; fish nutrition